Innovative approaches to integrative energy planning. Experiences and results from the EU project Urban Learning. - Gigler, Ute; Hemis, Herbert (My University, 2018)
Das EU-Projekt "Horizon 2020 - Urban Learning" (März 2015 - November 2017) umfasste sieben Hauptstädte (Wien, Berlin, Paris, Stockholm, Amsterdam, Warschau und Zagreb) sowie die Stadt Zaanstad (NL). Dabei ging es darum, Energie- und Stadtplanung zu integrieren und die Abkehr von fossilen Brennstoffen zu forcieren. Die Arbeit beschreibt das Projekt und nennt als einen wichtigen Erfolgsfaktor für gegenseitiges Lernen v. a. die Kooperation zwischen Städten und über Stadtbezirke hinweg sowie mit Stakeholdern wie Energieversorgern, Entwicklern und Planern.

Many cities in Europe and worldwide are searching for answers and effective approaches to the challenges of implementing ambitious climate objectives in liberalised energy markets while having to accomodate growing populations. Providing new infrastructure, jobs and affordable housing for city dwellers in urban areas offers unique chances for introducing renewables and largely decarbonised energy systems. At the same time, cities struggle with high building costs, urban planning approaches that only partially factor in energy planning as well as governance systems that would require much more collaboration and cooperation between key stakeholders involved in urban energy planning. The EU project Urban Learning (March 2015 November 2017) involved seven capital cities across Europe (Vienna, Berlin, Paris, Stockholm, Amsterdam, Warsaw and Zagreb) as well as the City of Zaanstad (NL) and focused on enhancing their capacity to work towards integrative energy planning through improved governance processes. All cities concentrated their efforts on improving governance processes in new development and transformation areas to fulfill their commitments for reducing the consumption of fossil fuels and to respond to the immediate pressure of population growth. The consortium analysed innovative technical solutions and their implications for planning processes, evaluated existing instruments and tools and explored ways to develop governance solutions that contribute to more effective integrative energy planning. In order to improve communication and interdepartmental exchange between key stakeholders from e.g. planning, sustainability or environmental departments, each partner city installed a so called Local Working Group. Intrinsic to the project design was a strong emphasis on learning from each other and on exchanging insights, barriers and lessons learned regularly between members of the consortium, with local working group members and with other associated cities from all partner countries throughout the entire project period. After 33 months of collaboration, a number of insights and results surfaced that can be passed on to other cities facing similar hurdles and wanting to improve their own (integrative) energy planning practices and capacities. Without a clear legal base and strategy for energy planning, integrating energy and urban planning will not work. Clear, long-term decarbonisation strategies further support cities paths toward achieving more integrated energy planning. It also showed that more awareness is required about the need for public energy planning competences in city administrations and beyond. A key success factor includes a constantly high level of cooperation and collaboration among and across city departments and with stakeholders such as energy system operators, energy suppliers, developers and planners. This paper describes lessons learned, insights and results from the Urban Learning project highlighting concrete examples from different partner cities.
Keywords: Kommunale Zusammenarbeit; Energieplanung; Stadtentwicklungsplanung; Integrierte Stadtentwicklung; Integrierte Planung; Energiekonzept; Energiewende; Kommunale Zusammenarbeit; EU